Economic Analysis of the Refugee Influx to Austria - Berger, Johannes; Strohner, Ludwig (Border Crossing, 2017)
This paper presents an economic assessment of the current refugee influx to Austria. Conclusions that can be drawn from Swedish experience suggest below average labour force integration of refugees, particularly in the first years after arrival. The skill composition of refugees is taken from surveys. The simulation model PuMA suggests a considerable employment increase, particularly of the unskilled workforce. This rise in employment remains, however, significantly below the number of additional refugees. The unemployment rate rises and is concentrated upon the refugees, but to a smaller extent unskilled residents are affected as well. Furthermore, wage developments of unskilled residents are below average. GDP per capita is negatively affected as a result of below average productivity and employment opportunities of refugees.